Persepsi Masyarakat terhadap Pemanfaatan Irigasi di Desa Waiketam Baru Kecamatan Bula Barat Kabupaten Seram Bagian Timur - Nurhayati, Nurhayati; D. Siwalette, Jeter; M. Puttileihalat, Paulus (Green Publisher Indonesia, 2025)
Rice is the main food commodity in Indonesia that relies heavily on the irrigation system to support agricultural productivity. However, the effectiveness of irrigation utilization is still a challenge for farmers, especially in Waiketambaru Village. This study aims to analyze the characteristics of farmers and the relationship between farmer characteristics and public perception of the use and utilization of irrigation. The novelty of this study lies in the in-depth analysis of socio-economic factors that affect farmers' perception of irrigation, which has not been widely studied in the context of the study area. This study uses a quantitative method with a survey approach, where data is collected through direct interviews with farmers in Waiketambaru Village. The sampling technique was carried out in a simple random sampling method (Simple Random Sampling), and the data analysis used regression and correlation statistical tests to identify the relationship between the research variables. The results of the study show that the main factors that affect farmers' perception of irrigation are productivity, level of knowledge, and the number of children they have. Farmers with high productivity and broader knowledge tend to have a better understanding of the benefits of irrigation systems. In conclusion, the optimization of irrigation systems must be supported by increasing farmers' knowledge and government policies that focus on education and sustainable management of water resources to improve farmers' welfare.